Factors Determining Bangladeshi University Students' Perception, Knowledge and Attitude About Climate Change: A Cross‐Sectional Study - Md. Mahadi Hassan; Md. Fakhrul Islam Maruf; Noushin Nohor; Anika Bushra Boitchi (Health Science Reports)
ABSTRACT Background and Aim Climate change refers to long‐term shifts in weather patterns and is one of the greatest global threats. Bangladesh is among the most vulnerable countries, facing severe climate‐induced events. Understanding climate change is crucial for identifying risks, developing adaptation strategies, and mitigating long‐term impacts. University students, as future leaders, play a vital role in addressing climate change. This study assesses their knowledge, attitudes, and perceptions of climate change in Bangladesh. Methods A cross‐sectional study was conducted among students from four universities in Bangladesh. A total of 1500 participants were selected based on inclusion criteria. Descriptive statistics summarized demographic characteristics, and perception regarding climate change, while univariate and multivariate logistic regression identified factors associated with good knowledge and positive attitudes. Results Overall, 73% of students had good knowledge of climate change, while 27% demonstrated poor knowledge. A majority (84%) expressed a positive attitude toward climate change initiatives. Participants correctly identified key climate‐related events in Bangladesh, such as increased cyclones, tidal waves, and salinity. However, awareness of rising snakebite incidents and related deaths was low, with many perceiving no change or disagreeing with their significance. Factors associated with good knowledge included gender, source of information, and mother's education. Gender, source of information, and both parents' education were associated with positive attitudes among the participants. Conclusions This study provides baseline evidence on climate change knowledge, attitudes, and perceptions among Bangladeshi university students. To our knowledge, it is the first comprehensive assessment of this issue in this population. Given their strong awareness and positive attitudes, targeted initiatives can harness students' potential in climate change mitigation and adaptation efforts, contributing to long‐term solutions for Bangladesh's climate challenges.